The Book of Great Books: A Guide to 100 World Classics - Campbell, W. John (New York : Barnes & Noble, Inc., 2000)
Entries for each work include a thumbnail historical background, main themes and symbols, insights into the language and style of the work, critical perspectives, and a character diagram.
Keywords: Literature -- History and criticism